-8+2f=3f

Simple and best practice solution for -8+2f=3f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+2f=3f equation:


Simplifying
-8 + 2f = 3f

Solving
-8 + 2f = 3f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-3f' to each side of the equation.
-8 + 2f + -3f = 3f + -3f

Combine like terms: 2f + -3f = -1f
-8 + -1f = 3f + -3f

Combine like terms: 3f + -3f = 0
-8 + -1f = 0

Add '8' to each side of the equation.
-8 + 8 + -1f = 0 + 8

Combine like terms: -8 + 8 = 0
0 + -1f = 0 + 8
-1f = 0 + 8

Combine like terms: 0 + 8 = 8
-1f = 8

Divide each side by '-1'.
f = -8

Simplifying
f = -8

See similar equations:

| 6x+6=-66-6 | | 6.2y-8.1=7.81+4.23y | | -23x+7y=-17 | | 1000.00+5000d=2200.00 | | 3y-3(6)+2x= | | 2x+30=5x-30 | | 12.5=y | | T+10-4r=-11 | | 3k+15+2x=5(x+5) | | 4x^2+y^2-3x+16y+124=0 | | .25x+.5y=7.75 | | 7*5+0.5*5= | | (3)3x=2x+20 | | Y=2x^3-4x^2+8 | | 5+21=x+13 | | 170-w=248 | | (9x-1)(5x+3)=0 | | 3x+11-6x-21=2 | | 3(6x-5)=6(x+4)-3 | | 5(-8x+12)= | | x^2+100=x^2+16 | | 4y=19+-7x | | (4)x=20 | | 2y-12=8 | | 0.95X+0.05(10-x)=0.10(-31) | | 2wp=p | | -7x^2-55x-42= | | 7x-4y=19fory | | 3-3a=12 | | X^3-12X^2+4X-30= | | 2w+13=49 | | 2wy=p |

Equations solver categories